Android Mobile Based Customer Policy Reminder Application - Delima Sitanggang; Sri Wahyuni Tarigan; Nova Riani Fransiska (Jurnal Mantik, 2020)
In the business world, the risks faced can be in the form of loss due to fire, damage, loss, or other risks. To reduce unwanted risks in the future, we need an insurance company that is willing to bear this risk, where every problem faced by its customers, whether individuals or business entities, is an insurance company that is willing and able to bear these risks. An insurance company that has many marketing agency offices. The payment system that has been running so far is carried out using a conventional process, where customers come to the company to make payments. However, there are many obstacles faced by customers when paying a policy such as not remembering the insurance policy number, due date, and the total premium that must be paid. With the design of the mobile andriod-based customer policy reminder application, it will make it easier for customers and the company. This android based mobile application design uses the Java Eclips program language, PHP, and is supported by the MySQL database. This android mobile-based customer policy reminder application will later provide flexibility, namely notification of payment due dates to customers when the customer uses the application, information about the share price of each unit in the company, information about hospitals in Indonesia that work with the company, and also convenience. for customers in making policy payments every month. The applications that have been implemented currently are credit card, home, motor vehicle, health, life, and education insurance